Fatal bus accidents: a legal review on policies governing the employment of express bus drivers / Nabeela Shakina Abdul Razak ...[et al.] - Abdul Razak, Nabeela Shakina; Md. Bohari, Nor Azimah; Abdul Shukor, Nurul Shafiah; Wan Bakri, Wan Nur Amalina (2011)
The study focused on the laws, policies, regulations and statutory evidences regarding the employment of express bus drivers. The increasing number of express bus accidents in Malaysia raised the question of what are the factors which lead to these fatalities. This research paper tries to tackle human factors contributing to occurrences of fatal accidents, i.e. the drivers. The study goes to seek how far had the law covered the welfare of the drivers and the steps and guidelines taken by the express bus operators in choosing their drivers. This research project also compared the policies and provisions under the United Kingdom's Transportation Laws regarding the express bus drivers. Few studies and reports on drivers' fatigue and stress also were analysed and its finding was incorporated under this research project. This research study purported to suggest the full legal enforcement of SHE COP 2007/2010 provisions on policies related to express bus drivers. Nonetheless, this research project paper also seeks to suggest several propositions to counter the shortcomings of express bus drivers' employment policies.